Energy awareness development process model - Mohammed, Abdul Hakim (Faculty of the Built Environment, University of Malaya, Kuala Lumpur, Malaysia., 2005)
The world should be reminded the event of oil crisis occurs in 1973 and 1978 because recently, enormous energy consumption once again become seriously while the energy resources are greatly reduce. Although new orientation have been carrying out by the governments to encourage use of alternative energy such as bio fuel, solar energy and biomass. But overall, it is too technology fixed. Practically, there are two kinds of energy saving: technological fixes and operational changes. Technological fixes is instrument base such as using motion sensor control lighting and air seal. However, technological fixes only is a temporary solution, it require no behaviour changes of the users, it mean the user still can waste energy in the same way. On the other hand, the operational changes are the soft technology that require changes of human behaviour, include both the facility manager and user. It is flexible and not so expensive compare to the previous. This research tends to explore the operational changes by examining the awareness of human being on energy conservation. The objectives of this research are to identify the factors that affect energy awareness and to develop an energy awareness conceptual and process model. Literature review and analysis will be carrying out to achieve the first and second objectives, the third objective will be achieved by using the questionnaire distribution and model evaluation. Expected output of this thesis is the energy awareness development process model. The rational of the study are possibility of the model to advance the energy management to a new level, provides a systematic energy awareness guideline to the facility manager, reduces the cost of energy conservation and ensures a better environment.